THE ROLE OF INTERACTION BETWEEN GOVERNMENT LEVELS IN SHAPING THE INVOLVEMENT OF EMPLOYEES IN INNOVATION ACTIVITIES: THE RESULTS OF THE EMPIRICAL ANALYSIS - G. Suzdaleva (Вестник университета)
Questions to increase innovative activity are relevant to today's enterprises. Factors influencing innovation activity - both negative and positive - there are so many. One of the groups of factors are the issues of personnel involvement in the processes of increase of innovative activity and stimulating innovation. The article presents the results of the pilot study of the effect of interaction between levels of government on increase of innovative activity of employees of enterprises of Perm and Perm region.